Paulo e Bartolomeu: dois meninos, tocante poesia. Dois homens, inquietante densidade. Considerações de uma professora contadora de histórias sobre as contribuições de Freire e Queirós na prática docente e na promoção da leitura literária - Ferreira, Hellenice de Souza (2019)
Under the title Paulo and Bartolomeu: two boys, touching poetry. Two men, unsettling density. Considerations of a storyteller teacher about Freire and Queirós’ contributions to the teaching practice and the promotion of literary reading I analize approximations in the authors' writings, pointing out to what extent Bartolomeu Campos de Queirós’ is important to the reading teachers who reflect on their daily practices, and pointing out how much Paulo Freire puts poetry on his texts, so that it is visible that both concur for a more relevant educational practice from their theoretical-literary productions. I use the interpretivequalitative method through which, after having reported my experiences in school units as reader and reading promoter and after having demonstrated writing cutouts of both, I try, through the memory of the lived, to confirm the hypothesis that their literatures, improving the reading experiences of the teachers, contribute to perfect their praxis in the classroom, turning them more fulfilled with meanings.